Therapeutic Potential of Heme Oxygenase-1 in Aneurysmal Diseases - Jiang, Wei-Cheng (Antioxidants (Basel), 2020)
Abdominal aortic aneurysm (AAA) and intracranial aneurysm (IA) are serious arterial diseases in the aorta and brain, respectively. AAA and IA are associated with old age in males and females, respectively, and if rupture occurs, they carry high morbidity and mortality. Aneurysmal subarachnoid hemorrhage (SAH) due to IA rupture has a high rate of complication and fatality. Despite these severe clinical outcomes, preventing or treating these devastating diseases remains an unmet medical need. Inflammation and oxidative stress are shared pathologies of these vascular diseases. Therefore, therapeutic strategies have focused on reducing inflammation and reactive oxygen species levels. Interestingly, in response to cellular stress, the inducible heme oxygenase-1 (HO-1) is highly upregulated and protects against tissue injury. HO-1 degrades the prooxidant heme and generates molecules with antioxidative and anti-inflammatory properties, resulting in decreased oxidative stress and inflammation. Therefore, increasing HO-1 activity is an attractive option for therapy. Several HO-1 inducers have been identified and tested in animal models for preventing or alleviating AAA, IA, and SAH. However, clinical trials have shown conflicting results. Further research and the development of highly selective HO-1 regulators may be needed to prevent the initiation and progression of AAA, IA, or SAH.